DIMENSI MCDONALISASI LAZADA ONLINE MALL: SEBUAH MODEL MODERNISASI SISTEM BELANJA - Lintang Citra Christiani (Jurnal Komunikasi dan Kajian Media, 2018)
The presence of an online mall website brings great consequences in public shopping habits. Lazada is one of the new means of consumption through a new media that offers a various easiness, which are visible as modern, practical, and efficient as management at a McDonald's fast food restaurant. McDonaldization theory from George Ritzer is used as a way to crack open the ideology and dimensions of McDonaldization and also its consequences. The results show that efficiency is not always free of charge. The principle of rationality just covers the risk of inefficiency in small amount, thus allowing more serious consequences such as dehumanization that leads to the minimization of humanitarian authenticity and homogenization that leads to technological dependence and loss of critical power.  Keywords: online mall, McDonaldization, George Ritzer, online shopping, e-commerce